We know that,
Root(a)*Root(b)=Root(ab)
Therefore,
Root(-16)*Root(-1) =Root{(-16)*(-1)}
=Root{16}
=4
But according to complex number concept,
Root(-16)*Root(-1)
=(4i) * (i)
=4(i)^2
=4(-1)
=-4

So, we got two results in two method. Let’s see which one is correct.

Actually, Root(a)*Root(b) =Root(ab),where a,b are non-negative number.

But here in first case we use -16 & -1 which are not non-negative number. So, because of wrong input the whole result becomes wrong in first case.

Since we know, Root(a)*Root(b) =Root(ab),where a,b are non-negative number. But if a,b are not non-negative number what we will do. How can we solve it? Actually, in that case, we have to use the concept of complex number what was done in second case.

So, the right answer is -4.